1993
DOI: 10.3171/jns.1993.78.3.0393
|View full text |Cite
|
Sign up to set email alerts
|

Chronic motor cortex stimulation in patients with thalamic pain

Abstract: Analysis of the authors' experience over the last 10 years has indicated that excellent pain control has rarely been obtained by thalamic relay nucleus stimulation in patients with thalamic pain. In the present study, 11 patients with thalamic pain were treated by chronic stimulation of the precentral gyrus. In eight patients (73%), the stimulation system was internalized since excellent pain control was achieved during a 1-week test period of precentral gyrus stimulation. In contrast, no clear effect was note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
289
1
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 495 publications
(306 citation statements)
references
References 44 publications
5
289
1
11
Order By: Relevance
“…Of the five patients with MCS, only one (20%) demonstrated better pain relief than with either DBS in the ventrocaudal nucleus of the thalamus (6/10, or 60%), SCS (6/19, or 32%), or a combination thereof. Tsubokawa's initial study in 1991 10 and a follow-up in 1993 45 demonstrated 5 of 11 patients with 'excellent' outcomes (defined as 100% improvement) at 2 years, compared with 6 of 12 in the first year; however, 3 of 12 patients who were defined as 'good' (60 -80% improvement) at 1 year dropped to either 'fair' (40 -60% improvement) or 'poor' (Ͻ40% improvement). These initial results nonetheless helped spur further investigation into MCS for pain.…”
Section: Introductionmentioning
confidence: 99%
“…Of the five patients with MCS, only one (20%) demonstrated better pain relief than with either DBS in the ventrocaudal nucleus of the thalamus (6/10, or 60%), SCS (6/19, or 32%), or a combination thereof. Tsubokawa's initial study in 1991 10 and a follow-up in 1993 45 demonstrated 5 of 11 patients with 'excellent' outcomes (defined as 100% improvement) at 2 years, compared with 6 of 12 in the first year; however, 3 of 12 patients who were defined as 'good' (60 -80% improvement) at 1 year dropped to either 'fair' (40 -60% improvement) or 'poor' (Ͻ40% improvement). These initial results nonetheless helped spur further investigation into MCS for pain.…”
Section: Introductionmentioning
confidence: 99%
“…[22]). In order to cover the largest surface above the motor cortex two electrodes (Resume, Medtronic,USA), each with four contacts (diameter: 4 mm, center to center distance: 10 mm), were secured on the dura mater.…”
Section: Datamentioning
confidence: 99%
“…34) Over the next 20 years, the indications for EMCS expanded to include neuropathic pain, 24,26,30) the recovery of motor paresis after stroke, 2) Parkinson's disease, 4) and dystonia. 25) In 1985, Baker established transcranial magnetic stimulation (TMS), as a non-invasive method for cortical stimulation that could be used for physiological examination.…”
Section: Introductionmentioning
confidence: 99%